POTENTIAL RECOVERY FROM HEPATOTOXICITY BY OPERCULINA TURPETHUM AND ITS ISOLATED STIGMA-5,22DIEN-3-O-B-DGLUCOPYRANOSIDE AGAINST N- NITROSODIMETHYLAMINE, A POTENT CARCINOGEN IN ANIMAL MODEL - VEENA SHARMA,; MANU SINGH, (International Journal of Pharma and Bio Sciences, 2014)
N-Nitrosodimethylamine is one of the main N-nitroso compound,commonly found in drinking water and is a potent hepatotoxin, carcinogen and mutagen. The curative effect of ethanolic root extract of Operculina turpethum was studied for its possible hepatoprotective potential against N- Nitrosodimethylamine in Swiss albino mice. Hepatic malondialdehyde (MDA), Superoxide dismutase(SOD),catalase(CAT),glutathione content(GSH),aspartate aminotransferase (AST), alanine aminotransferase (ALT), alkaline phosphatise (ALP), protein, cholesterol and bilirubin content were measured as oxidant/antioxidant markers. Parallel Electron Microscopical investigations were also performed. One-way ANOVA test was used for comparisons of parameters in study groups. Oral administration of Operculina turpethum extract and isolated compound recovered the levels as compared to NDMA group. Furthermore, it prevented the depletion in biochemical marker levels at the significant levels of (p<0.01) and (p>0.05).The ultrastructural electron microscopy showed a decrease in cellular degradation comparing to the intoxicated mice. A critical analysis of results of these studies suggested hepatoprotective potential of the plant, suitable for use as a supportive complementary medicine in liver cancer.